Association between baseline cardio-kidney-metabolic syndrome, its transition and cognitive impairment: result from CHARLS study - Yuanyue Zhu; Xuejie Wang; Kan Wang; Yiming Dai; Weiguo Hu; Yufang Bi; Linhui Shen (Diabetology & Metabolic Syndrome)
Abstract Aims Cardiovascular-Kidney-Metabolic (CKM) syndrome is an integrated context encompassing diabetes, obesity, cardiovascular, and chronic kidney diseases. The impact of CKM syndrome on cognitive impairment remained unclear. Methods This longitudinal, observational study used data from the China Health and Retirement Longitudinal Study waves 1 and 4 (2011 to 2018). In total, 8,833 participants were included for the analysis between baseline CKM and cognitive impairment, and 4,230 were included for the analysis between CKM transition and cognitive impairment. Baseline CKM were classified into 5 consecutive stages according to the AHA statement, and transitions in CKM stages were classified as improved, stable, or progressed based on the difference in states between 2011 and 2015. Logistic regressions were used to explore the associations between CKM stages, transitions and the risk of subsequent cognitive impairment. Result Compared with those in stage 0, the adjusted odds ratio [95% confidence intervals] (aOR [95% CI]) of incident cognitive impairment were 1.74 (1.00-3.18) for stage 1, 2.05 (1.17-3.81) for stage 2, 2.09 (1.27-3.66) for stage 3, and 3.91 (2.33-6.99) for stage 4, respectively. The odds ratios were higher among male and elder participants. In the transition analysis, the aOR (95% CI) was 0.44 (0.19-1.03) for improved group and 1.61 (1.01-2.59) for progressed group, compared with the those maintaining stable CKM stages. Conclusions Higher CKM stages are associated with incrementally elevated risk of cognitive impairment. Additionally, the progression of CKM stages corresponded with greater hazards of cognitive impairment, while stage reversion might be associated with reduced risk.